2013
DOI: 10.1111/all.12236
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, cross-reactivity, and specificity of Bet v 1-specific IgG4 antibodies induced by immunotherapy with birch pollen

Abstract: Our results indicate that BP-SIT may induce Bet v 1-specific IgG4 antibodies that cross-react with related food allergens and inhibit IgE binding by epitope competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 37 publications
4
53
1
Order By: Relevance
“…This pathophysiology is reminiscent of other, so‐called secondary food allergies, for example birch pollen‐related food allergy. Here, sensitization occurs to Bet v 1 via the respiratory tract and allergic reactions to foods are caused by IgE reactivity to similar conformational epitopes on structurally related food proteins, for example Mal d 1 in apple 29. We present 20 Austrian patients with delayed meat allergy and IgE reactivity to α‐gal on bovine IgG.…”
Section: Discussionmentioning
confidence: 99%
“…This pathophysiology is reminiscent of other, so‐called secondary food allergies, for example birch pollen‐related food allergy. Here, sensitization occurs to Bet v 1 via the respiratory tract and allergic reactions to foods are caused by IgE reactivity to similar conformational epitopes on structurally related food proteins, for example Mal d 1 in apple 29. We present 20 Austrian patients with delayed meat allergy and IgE reactivity to α‐gal on bovine IgG.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a different type of AIT, namely, subcutaneous treatment with birch pollen extract (BP-AIT) containing 5% to 10% of the sole major allergen Bet v 1, we have reported that most Bet v 1-specific IgG 4 antibodies induced after 36 months recognized IgE epitopes and only a minority represented de novo specificities. 2 In the present longitudinal study, we sought to investigate whether the diversity of Bet v 1-specific IgG 4 antibodies expands, decreases, or remains similar in the course of BP-AIT.…”
Section: To the Editormentioning
confidence: 99%
“…2 Briefly, each serum sample was preincubated with Bet v 1 and the same indicator serum containing more than 100 kU/L of Bet v 1-specific IgE with a presumed highly diverse IgE repertoire. Thereafter, the activity of each serum to reduce the binding of Bet v 1-IgE complexes to CD23 1 B cells was determined.…”
Section: To the Editormentioning
confidence: 99%
“…Although the BT-specific IgG 4 increase was small, it was statistically significant. This may explain part of the therapeutic effect, similar to the cross-reactive IgG 4 to tree species, such as alder and hazel, induced with birch pollen immunotherapy [35]. …”
Section: Discussionmentioning
confidence: 99%